Does aging influence sectoral employment shares? Evidence from panel data - Ulrich Thiessen; Konstantin A. Kholodilin; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2008)
Our study represents a first attempt to single out the effects of aging on the entire structure of the economy that is approximated by employment shares in different sectors. We find that even after controlling for the effects of other relevant factors - e.g. income per capita, share of trade in GDP, government consumption share in GDP, population size - aging does have a statistically significant differentiated impact on the employment shares. In particular, we find that an increase in the aging proxies exerts a statistically significant adverse effect on the employment shares in agriculture, manufacturing, construction, and mining and quarrying industries. At the same time, increasing share of the elderly people in the society positively affects employment shares in community, social, and personal services as well as in the financial sector. In the simulation exercise, we illustrate the effects of aging on the employment structure within the next 45 years.
Keywords: J11; O57; C33; 330; Structural change; aging; employment shares; dynamic panel data; Sektorale Beschäftigungsstruktur; Alternde Bevölkerung; Strukturwandel; Drei-Sektoren-Hypothese; Welt